Polymer Solar Cells: Enhanced Charge Separation Efficiency in DNA Templated Polymer Solar Cells (Adv. Funct. Mater. 26/2018). (25th June 2018) - Toschi, Francesco; Catone, Daniele; O'Keeffe, Patrick; Paladini, Alessandra; Turchini, Stefano; Dagar, Janardan; Brown, Thomas M.
Abstract : Ultrafast pump–probe optical spectroscopy on polymer solar cells shows that when DNA is used as a nanointerlayer between the electron‐transport (ZnO nanoparticles) and photoactive layers, the DNA imprints a long‐range order on the polymeric photoabsorber, leading to enhanced charge separation, as described by Patrick O'Keeffe and co‐workers in article number1707126 .